ANALISIS PENGARUH PERILAKU DISIPLIN TERHADAP PRESTASI TARUNA DI LINGKUNGAN KEMENTERIAN PERHUBUNGAN - Sirait, Donna N.M; Akbar, Muhammad Caesar; Lumban Gaol, Erwin; ARITONANG, ARIOS (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Educational institutions carry the mandate to control the development of education in accordance with the implementation of Nawacita in various priority work programs of the ministry. The Ministry of Transportation sees global trends related to technological advances, socio-cultural shifts, environmental changes, and differences in the future world of work in education at every level. The development of technology makes education more advanced and an important part of the development of education to meet the demands of an increasingly competitive era.